The Process of Managing Cultural Heritage by Local Politicians in Nong Khai Province: The Process of Managing Cultural Heritage by Local Politicians in Nong Khai Province - Phuttajorn, Apiwatchai; Mahasamitthi (Attasarn), Phramaha Somdet; Phrakru Sutasarabandit; Varundee, Kid; Paññāvaḍḍhano (Polsri), Phramaha Chatchai; Candasãro (Moohuana), Phra Sittirak; Pariyattimedhi (Yotajan), Phramaha Thanawat (RATANABUTH JOURNAL, 2026)
This research aims to 1) study the cultural heritage and development potential of local politicians in Nong Khai province, 2) study the policies and approaches to cultural heritage development of local politicians in Nong Khai province, and 3) analyze the cultural heritage management process of local politicians in Nong Khai province. This is a qualitative research study, using triangulation to verify the accuracy and reliability of the data through a comparison of data from documents, academic papers, and field data obtained from interviews with 18 key informants. The results are presented in a descriptive analytical format. The research findings revealed that: 1) Cultural Heritage and Development Potential: Nong Khai Province possesses diverse cultural heritage encompassing physical, intangible, intellectual, artistic, religious, and linguistic aspects. This contributes to community identity and drives economic growth through tourism. Its strategic location as a gateway to Laos provides high potential for sustainable cultural tourism development, despite facing challenges related to budget constraints and overtourism. 2) Policies and Development Guidelines for Cultural Heritage: Local politicians have adopted a strategy of balancing conservation and economic development, elevating cultural heritage as an economic resource while promoting knowledge and community participation. This is within a legal framework supporting protection, decentralization, and monitoring, focusing on infrastructure development, tourist attraction, and rigorous enforcement of local laws. 3) Cultural Heritage Management Process: The management process prioritizes community participation at three levels: conservation, development, and policy formulation. Supporting strategies include raising awareness, providing incentives, establishing partnerships, and utilizing digital technology. This fosters a sense of shared ownership, economic development, and strong collaborative networks for the sustainable preservation of cultural heritage in all dimensions.